2010
DOI: 10.1088/1674-4926/31/3/036001
|View full text |Cite
|
Sign up to set email alerts
|

Wet etching characteristics of a HfSiON high-kdielectric in HF-based solutions

Abstract: The wet etching properties of a HfSiON high-k dielectric in HF-based solutions are investigated. HF-based solutions are the most promising wet chemistries for the removal of HfSiON, and etch selectivity of HF-based solutions can be improved by the addition of an acid and/or an alcohol to the HF solution. Due to densification during annealing, the etch rate of HfSiON annealed at 900 ı C for 30 s is significantly reduced compared with as-deposited HfSiON in HF-based solutions. After the HfSiON film has been comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…[16] Meanwhile, compared with 1% DHF used to remove HfSiON dielectric, DHF/HCl/alcohol solution could achieve not only a high etch rate (from 6.1 nm/min to 11.9 nm/min) but also high selectivity of HfSiON to SiO 2 (from 3.47 : 1 to 20.5 : 1). [17] In addition, it is found that the pMOS high-k PDA process not only affects first deposited nMOS thermal budget but also influences the a-Si hardmask removal of nMOS since a-Si may change into poly-Si under high temperature and cannot be removed by NH 4 OH solution. So, lower HfSiAlON PDA(600 • C, 60 s) is a practicable method for DHDMG process without obviously electrical influence since S/D activation annealing can provide enough thermal quantity to form Al-O dipoles at the interface between high-k and bottom SiO x (already verified by the pMOS MIPS structure capacitor in Subsection 3.1).…”
Section: Separating Of High-k and Metal Gate For N/pmosmentioning
confidence: 99%
“…[16] Meanwhile, compared with 1% DHF used to remove HfSiON dielectric, DHF/HCl/alcohol solution could achieve not only a high etch rate (from 6.1 nm/min to 11.9 nm/min) but also high selectivity of HfSiON to SiO 2 (from 3.47 : 1 to 20.5 : 1). [17] In addition, it is found that the pMOS high-k PDA process not only affects first deposited nMOS thermal budget but also influences the a-Si hardmask removal of nMOS since a-Si may change into poly-Si under high temperature and cannot be removed by NH 4 OH solution. So, lower HfSiAlON PDA(600 • C, 60 s) is a practicable method for DHDMG process without obviously electrical influence since S/D activation annealing can provide enough thermal quantity to form Al-O dipoles at the interface between high-k and bottom SiO x (already verified by the pMOS MIPS structure capacitor in Subsection 3.1).…”
Section: Separating Of High-k and Metal Gate For N/pmosmentioning
confidence: 99%
“…To find the interaction between etch rate and different apertures, and the relationship between etch rate and different pitches, we select two kinds of periodic patterns in our study [4] . The aperture size of the first kind of periodic patterns is equal with the pitch of the pattern, the length of each apertures is 4μm, 6μm, 8μm, 10μm, 12μm, 14μm, 16 μm, respectively.…”
Section: The Effect Of Periodic Patterns Sizementioning
confidence: 99%